2011
DOI: 10.1038/hr.2011.163
|View full text |Cite
|
Sign up to set email alerts
|

Nitrergic nerves derived from the pterygopalatine ganglion innervate arteries irrigating the cerebrum but not the cerebellum and brain stem in monkeys

Abstract: The functional roles of the nitrergic nerves innervating the monkey cerebral artery were evaluated in a tension-response study examining isolated arteries in vitro and cerebral angiography in vivo. Nicotine produced relaxation of arteries by stimulation of nerve terminals innervating isolated monkey arteries irrigating the cerebrum, cerebellum and brain stem. Relaxation of arteries induced by nicotine was abolished by treatment with N G -nitro-L-arginine, a nitric oxide synthase inhibitor, and was restored by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…At the end of most experiments, the preparations were additionally challenged with nicotine (100 µmol/L). The amplitude of nicotine-induced relaxation was similar to that induced by EFS (10 Hz) in y-BA consistent with other reports 16 and was significantly ( p < 0.001) smaller in o-BA (Figure 4(a)). In y-BA, nicotine-induced relaxation was significantly attenuated by TTX or L-NPA ( p < 0.05, Figure 4(a)).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…At the end of most experiments, the preparations were additionally challenged with nicotine (100 µmol/L). The amplitude of nicotine-induced relaxation was similar to that induced by EFS (10 Hz) in y-BA consistent with other reports 16 and was significantly ( p < 0.001) smaller in o-BA (Figure 4(a)). In y-BA, nicotine-induced relaxation was significantly attenuated by TTX or L-NPA ( p < 0.05, Figure 4(a)).…”
Section: Resultssupporting
confidence: 91%
“…A novel experimental therapeutic approach in animal models is the stimulation of the sphenopalatine ganglion 14 which leads to vasodilation, likely by releasing NO from perivascular neurons. 15,16 Histological and electrophysiological studies have demonstrated that cerebral arteries are innervated predominantly by preganglionic neurons originating from the superior salivatory nucleus, which via the great petrosal nerve and sphenopalatine ganglion, and after switching to small postganglionic neurons, innervate cerebral arteries and intracranial internal carotid arteries, as well as the vasculature of the lacrimal and nasal glands. 17 These neurons release NO and peptides like substance P, vasoactive intestinal polypeptide and calcitonin gene-related peptide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In monkeys, PPG fibres appeared to be the source of NOS‐positive fibres to the anterior but not posterior cerebral arteries (Ayajiki et al . ) and in rats parasympathetic VIP‐ (Hara et al . ) and NOS‐positive fibres (Nozaki et al .…”
Section: Origin Of Parasympathetic Fibres To the Posterior Cerebral Amentioning
confidence: 99%
“…Se ha demostrado en modelos animales que la estimulación eléctrica del nervio facial incrementa el flujo sanguíneo cerebral [17][18][19][20][21][22]. En un estudio con monos en el que se estimuló eléctricamente el nervio petroso mayor, que conecta con el ganglio pterigopalatino a través de la sinapsis con el ganglio parasimpático, se observó vasodilatación de las arterias cerebrales anterior, media y posterior en el lado estimulado [23]. Esto sugiere fuertemente la implicación de los componentes parasimpáticos que se originan en el tronco del nervio facial cerca del ganglio geniculado para formar los nervios petroso, que luego inervan las grandes arterias cerebrales a través de la ganglio pterigopalatino.…”
Section: Nervio Facialunclassified